2010
DOI: 10.1111/j.1365-2796.2010.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized, controlled trial of intravenous versus oral iron for moderate iron deficiency anaemia of pregnancy

Abstract: Background. Iron deficiency anaemia is the most common deficiency disorder in the world, affecting more than one billion people, with pregnant women at particular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(144 citation statements)
references
References 18 publications
5
133
3
3
Order By: Relevance
“…Second; the relatively short preoperative duration of treatment with oral iron in some patients, is arguably not sufficient to replete the iron stores. This perhaps proves the point for effectiveness of IV iron in replenishing the iron stores in a shorter period of time compared to oral iron as seen in other cohort of patients [25,33]. The IV iron group was also able to maintain the Hb for a longer period of time compared to oral iron.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Second; the relatively short preoperative duration of treatment with oral iron in some patients, is arguably not sufficient to replete the iron stores. This perhaps proves the point for effectiveness of IV iron in replenishing the iron stores in a shorter period of time compared to oral iron as seen in other cohort of patients [25,33]. The IV iron group was also able to maintain the Hb for a longer period of time compared to oral iron.…”
Section: Discussionmentioning
confidence: 62%
“…Recent reports demonstrate the feasibility of rapid iron polymaltose infusion over 90 minutes [33,34]. However, a test-dose of iron polymaltose (100 mg) should be first administered over 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…14 A study published by Khalafallah et al also did not find any difference in birth weight in IV iron arm vs. 18 oral iron arm. However they used iron polymaltose instead of iron sucrose.…”
Section: Discussionmentioning
confidence: 89%
“…There has been a recent interest in the use of ferric carboxymaltose which can be given in a single dose and it promises to be more effective, well tolerated and has a comparable safety profile to iron sucrose reducing the need for repeated injections and increases the patients comfort and thus compliance. 18 Further research is required to study its effect in the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%
“…33 Several studies have indicated that intravenous iron acts faster and DOI:10.1002/MSJ more effectively and is better tolerated compared with oral iron in various populations. 34,35 Intravenous iron preparations are available with various formulations (ie, iron dextran, iron sucrose, iron gluconate, and recently approved ferumoxytol), each with specific characteristics to treat iron-deficiency anemia. 36 Given the concerns associated with ESAs, the role of intravenous iron has become even more important as the primary therapy for anemia, and as an adjuvant to ESA therapy, to improve efficiency and decrease the ESA dose.…”
Section: Preoperative Preparationmentioning
confidence: 99%